Ice sheet surface lineaments as nonconventional indicators of East Antarctica bedrock tectonics - CIANFARRA, Paola; SALVINI, Francesco (Geosphere, 2014)
A recent focus of major international exploration in East Antarctica has been aimed at revealing its bedrock topography and imaging its tectonic architecture and evolution. Here we present the tectonic interpretation of regional-scale lineaments revealed by the Radarsat mosaic of Antarctica on the ice sheet surface in the Vostok–Dome C– Adventure Basin region. These lineaments appear in the radar backscatter textures as alignments of marked tonal variations with lengths of tens to hundreds of kilometers and were identifi ed using an automated methodology. We explore the origin scenarios for the ice sheet surface lineaments by comparing their azimuthal trends and spatial distribution with the main morphotectonic features of the bedrock. Azimuthal analysis reveals that lineaments cluster around two preferential directions interpreted as structural or tectonic domains. These show strong correlations with azimuths of tectonic fabrics in the bedrock. The main lineament domain parallels the morphotectonic features of the study area, namely the Adventure Basin and the Concordia and Aurora Trenches. The second lineament set corresponds to the mean orientation of the Lake Vostok depression. The spatial analyses of the two lineament domains strengthen our fi ndings and interpretations. Comparisons with wind and ice fl ow directions exclude their infl uence on the identifi ed lineament pattern. Results reveal the tectonic origin of the lineament domains, and demonstrate the method’s usefulness as a tool for tectonic studies of regions characterized by thick covers. These regions include other areas of the East Antarctic craton such as the Gamburtsev Subglacial Mountains, as well as deserts or surfaces of other planets.